Genetic polymorphisms of the folate cycle and hyperhomocysteinemia in children from areas bordering the Chоrnobyl exclusion zone (Environment & Health, 2023)
The aim of the work is to establish a relationship between polymorphisms of the FC and the state of hyperhomocysteinemia in children living in areas bordering the ChEZ).Research methods: laboratory, genetic, mathematical-statistical.Results: The levels of homocysteine (Hcy) in blood and genetic polymorphisms of the folate cycle (FC) were determined in 690 children (322 boys and 368 girls) aged 8-17 years old living near the ChEZ. It was found that 97.8% of the children had genotypes with risk alleles of FC polymorphisms. The most common combinations of 2 and 3 polymorphic variants.The proportion of hyperhomocysteinemia cases was recorded in 62.5% of those examined and did not generally depend on the number of FC polymorphisms with risk alleles. Unlike their mothers, there was no correlation between blood Hcy concentration and the number of FC polymorphisms with risk alleles in children.The frequency of hyperhomocysteinemia cases in boys was likely higher than in girls. Hyperhomocysteinemia was detected in 40% of cases among children with no risk alleles for FC genetic polymorphisms.Genotypes with allele variants of one FC polymorphism were found in 15% of cases. High frequency of hyperhomocysteinemia was recorded both in the subgroup with T/T MTHFR:677 genotype and in most genetic subgroups.A high frequency of hyperhomocysteinemia, with four polymorphisms with risk alleles, was associated with compound heterozygotes A/CMTHFR:1298 and C/TMTHFR:677 in combination with A/G MTR genotypes: A2756G and G/G A66G.The homozygous variant of the neutral allele A of the MTRR:A66G genetic polymorphism, which controls methionine synthase reductase, contributed to the improvement of Hcy methylation processes in risk allele variants of three FC polymorphisms.Conclusions: The conducted studies indicate that in children of the second Chоrnobyl generation, who have been living in conditions of constant radiation exposure in areas affected by the Chоrnobyl accident since birth, the occurrence of hyperhomocysteinemia is not associated with a specific genotype and the number of FC polymorphisms with risk alleles. The results obtained indicate the participation of genetic and environmental factors in the occurrence of hyperhomocysteinemia in the population of children living in areas located near the ChEZ.
Keywords: hyperhomocysteinemia; folate cycle genes; risk alleles; children; Chоrnobyl Exclusion Zone